2021
DOI: 10.1016/j.heliyon.2021.e06537
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body aspiration in a tertiary Syrian centre: A 7-year retrospective study

Abstract: Background: Paediatric foreign body aspiration constitutes significant lethal sequela worldwide. This is the first descriptive Syrian study that aims to describe the epidemiology of foreign body aspiration in a tertiary centre in Syria. Methods: This is a retrospective cohort study conducted at the Children's University Hospital, Damascus, from 2011 to 2018 during the Syrian crisis. The children underwent rigid bronchoscopy at Al Mouwasat University hospital, the only properly equipped hospital to perform paed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Immediate and accurate diagnosis of FBA can be a lifesaver, especially in small children who may choke unwitnessed. Our findings align with previous studies indicating that FBA is most commonly observed in children aged 1-2 years (3)(4)(5). Notably, the most vulnerable age group for FBA cases is under three years old (6), and our study reflects this age distribution, with two-thirds of FBA cases being male (2,3,6).…”
Section: Discussionsupporting
confidence: 92%
“…Immediate and accurate diagnosis of FBA can be a lifesaver, especially in small children who may choke unwitnessed. Our findings align with previous studies indicating that FBA is most commonly observed in children aged 1-2 years (3)(4)(5). Notably, the most vulnerable age group for FBA cases is under three years old (6), and our study reflects this age distribution, with two-thirds of FBA cases being male (2,3,6).…”
Section: Discussionsupporting
confidence: 92%